Network literature and traditional literature: comparative analysis - Tzui , Hunyan (Journal of the Belarusian State University. Philology, 2024)
Network literature is considered as a special form of literature. Its boundaries are determined. The differences between network literature and traditional literature are established. The features of network literature are clarified, determined both by the digital form of existence of works (virtuality, nonlinearity, cyclicity, integrativeness, multimedia), and by the method of their creation, distribution and consumption (fragmentation, high availability, internationality, relevance). It is proved that one of the most important features of network literature is interactivity, manifested in active communication between authors and readers. It is confirmed that posting works on the Internet provides greater freedom of creative expression than publishing them in a traditional format.